Research progress on the association of bullous pemphigoid with type 2 diabetes mellitus - ZHANG Ruohan; WANG Zhenying (Pifu-xingbing zhenliaoxue zazhi)
Bullous pemphigoid (BP) is a common autoimmune bullous disease that predominantly affects the elderly. The incidence of diabetes mellitus (DM) is higher in BP patients than in the general population, and the coexistence of diabetes is considered an adverse prognostic factor in BP patients. A substantial amount of epidemiological evidence has demonstrated an association between the two conditions. The link between them may be influenced by factors, such as age, immune status, use of medication, and genetic predisposition. However, their causal relationship remains unclear. Early monitoring of blood glucose levels in BP patients and the selection of appropriate treatment strategies are crucial for controlling the disease and improving prognosis. This review describes the relationship between the two conditions from the aspects of epidemiology, pathogenesis, clinical characteristics, and treatment, in order to provide references for further research into their connection and potential mechanisms.